Attitude and Heading Reference System for Aerospace Application - B, Kirthana; K, Madhushree; MS, Madhushree; S, Dhanraj; P H, Megha (International Journal of Computer Sciences and Engineering, 2025)
Many experiments have been conducted for attitude estimation with low cost micro electro-mechanical system (MEMS), even though it was of low cost and less weight it causes certain noise and errors over time. The main objective of the paper is to introduce accelerometer portion of basic attitude and heading reference system for aerospace application using Internet of Things (IoT) which can be used to find the optimal weight value such error of the Attitude and Heading Reference (AHRS) is minimised. The proposed system also assures the body rate by using 2 axis gyro and it provides distance rate measurement and angular rotation. This system consumes low power and easy to handle